Results of case-control studies support the association between contact lens use and Acanthamoeba keratitis - Pacella E (Dove Medical Press, 2013)
Elena Pacella,1 Giuseppe La Torre,2 Maria De Giusti,2 Chiara Brillante,1 Anna Maria Lombardi,2 Gianpaolo Smaldone,1 Tommaso Lenzi,1 Fernanda Pacella11Department of Sense Organs, Faculty of Medicine and Dentistry, Sapienza University of Rome, Italy; 2Department of Public Health and Infectious Diseases, Faculty of Pharmacy and Medicine, Sapienza University of Rome, ItalyBackground: Acanthamoeba keratitis (AK) is ever more frequently reported in industrialized countries. The loss of the corneal surface integrity consequent to secondary microtrauma produced by the use of contact lens (CL) favors the penetration of the parasite into the corneal tissue.Objectives: A scientific review was performed to investigate the association of CL wear as an Acanthamoeba keratitis (AK) risk factor.Methods: A computerized screening of 7834 Medline articles (4623 from PubMed; 3211 from Scopus) used a strict selection criteria of case-control studies involving CL wear and/or trauma.Results: The search yielded five case-control studies published from 1995 to 2012. All studies included showed a statistically significant positive association between AK and CL use, with a combined odds ratio (OR) of 10.21 (95%, confidence intervals [CI]; 3.57–27.64).Statistical analysis: All studies included showed a statistically significant positive association between AK and CL use, though with differing OR values.Conclusion: Though rare, AK should be held in higher consideration when ophthalmologists are faced with CL users exhibiting simplex-like lesions associated with circular stromal infiltrates and disproportionate ocular pain in respect to the objective clinical picture.Keywords: keratitis, contact lens, Acanthamoeba